GILaS (Science Literacy Activities) through Simple Experiments for Students at St. Paulus Karuni Middle School - Geterudis Kerans; Oktavianus Deke; Ni Wayan Prawita Aryani; Khristoforus Palli Ngongo; Angela Ghunu; Falentina Tamo Ina (Carmin: Journal of Community Service, 2026)
Scientific literacy is essential for students to develop their scientific abilities. Indonesian students' performance in this area is still very low, as shown by the 2018 PISA results. To address this issue, schools need to provide support to students. Through this community service program, a solution is offered by conducting GILaS through simple experiments for St. Paulus Karuni Middle School students. The main objective of this community service program is to strengthen students' scientific literacy through simple experiments. Through the experimental method, students are actively involved so they can understand the steps and results of the experiment, thereby strengthening their scientific literacy. The participants were 42 students, 16 male and 26 female. The evaluation instrument used was a student response sheet on the implementation of the activity. The instrument contained four main indicators: 1) interest and motivation to learn, 2) understanding of the material, 3) implementation and mentoring, and 4) general benefit. The results of the activity showed that students responded positively to the GILaS activity, with response rates of 65.28 percent strongly agree, 31.15 percent agree, 1.79 percent disagree, and 0.79 percent strongly disagree. GILaS activities are essential, especially for schools with limited laboratories and those that have never conducted practical work at school. This activity is an important part of a collaborative effort to strengthen students' scientific literacy.